INNOVATIVE ECONOMY IN AGRICULTURE: DRIVING TRANSFORMATION AND SUSTAINABILITY (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
The agricultural sector has long been a cornerstone of global economies, but the demands of modern society and environmental challenges require a transformation. This article explores the concept of an innovative economy in agriculture, highlighting the integration of technology, sustainable practices, and new economic models to revolutionize the industry. By focusing on technological advancements such as precision farming, digital tools, and sustainable agricultural practices, the article presents an overview of how innovation is reshaping agricultural economies. The results of these innovations demonstrate increased productivity, improved resource efficiency, and enhanced sustainability, laying a foundation for long-term agricultural development.